Comparative Study Between Global and Local Gamma Index for Evaluating Volumetric Modulated Arc Therapy (VMAT) for Prostate Cancer - Mustafa I. Ahmed Aldulaimy; Ahmed Suhail (Academia Open, 2026)
General Background: Prostate cancer is a major malignancy among men, and Volumetric Modulated Arc Therapy (VMAT) is widely used in radiotherapy to deliver precise radiation doses while protecting surrounding organs at risk. Specific Background: The gamma index is commonly applied in radiotherapy quality assurance to evaluate agreement between planned and delivered dose distributions using global and local calculation methods. Knowledge Gap: However, uncertainty remains regarding which gamma index method provides more reliable verification for VMAT prostate cancer treatment. Aims: This study compares global and local gamma index approaches in evaluating VMAT treatment plans. Results: A prospective study involving 30 prostate cancer patients showed that VMAT achieved high tumour coverage (V98% = 97.03%) with minimal dose spread (V5% = 0.35%). The global gamma index consistently produced higher pass rates than the local gamma index across verification criteria (3%/3 mm: 0.95 vs 0.92; 2%/2 mm: 0.93 vs 0.81; 1%/1 mm: 0.69 vs 0.60) with significant differences. Novelty: The study provides comparative evidence of global and local gamma index performance in VMAT verification. Implications: The findings support the global g Highlights:• Vmat Planning Achieved High Target Coverage With V98% Reaching 97.03%.• Global Gamma Evaluation Produced Consistently Higher Pass Rates Across All Verification Criteria.• Significant Statistical Differences Observed Between Global and Local Dose Agreement Metrics. Keywords: Prostate Cancer, Volumetric Modulated Arc Therapy, Gamma Index, Radiotherapy Quality Assurance, Dose Verification